Iowa, fall 1996 documentations, December 11, 1996 - Iowa Ornithologists' Unionet al (1996)
A list of documented bird sightings organized by species, December 11, 1996. The list also contains the number of birds seen, date of sighting, location, and observer of each species. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed